The Use Of Listen Read Discuss (LRD) Strategy To Improve Student’s Reading Comprehension - Adelia, Adelia; Darmawan, Darmawan (STKIP Yapis Dompu, 2021)
The objective of this research is to find out whether the use of LRD Strategy can improve reading comprehension of grade ten students particularly in descriptive text. This researcher applied a quasi-experimental research design. The population of this research was grade ten students of SMK Negeri 6 Palu which consist of 108 students. The sample of this research was 36 students of class X TKJ 2 and considered as the experimental class while 36 students of class X TKJ 3 as the control class. The sample was selected using cluster random sampling technique. The technique of data collection was test that includes pre-test and post-test. While the mean score of pre-test in experimental class was about 49.71, the control class is 58.09. In post-test, experimental class got 64.76. On the other hand, the control class got 61.13. By applying 0.05 level of significance and 28 degree of freedom (df), as seen tha table that the value of t-counted is (2.12) and t-table is (1.703). The t-counted value is higher than t-table, which means that the research hypothesis is accepted. Therefore, the use of LRD Strategy can improve students’ reading comprehension in descriptive text.